Alexandria : historical and archaeological guide - Ḥusnī, Yusrīyah ʻAbd al-ʻAzīz. (Supreme Council of Antiquities, 2009)
"Gives an overview of all the historical sites in and around Alexandria, from the earliest Ptolemaic remains submerged under the sea, through the Greco-Roman catacombs, to the Jewish, Christian, and Islamic landmarks of the city. All the city's museums are also covered"--American University in Cairo Press (distributor) Web site, 20 Apr. 2012.